Respuesta :

The solution to the given inequality is; x ≥ -9/4 or x ≥ 1

How to solve Inequality problems?

We want to solve the inequality;

(4x² + 5x - 9)/(x² - x - 6) ≥ 0

Let us factorize both numerator and denominator to get;

4x² + 5x - 9 = (4x + 9)(x - 1)

Similarly, x² - x - 6 when factorized gives;

x² - x - 6 = (x + 2)(x - 3)

Thus, we now have;

[(4x + 9)(x - 1)]/[(x + 2)(x - 3)] ≥ 0

Multiply both sides by [(x + 2)(x - 3)] to get;

(4x + 9)(x - 1) ≥ 0

Thus;

(4x + 9) ≥ 0 or (x - 1) ≥ 0

Thus;

x ≥ -9/4 or x ≥ 1

Read more about Inequality at; https://brainly.com/question/25275758

#SPJ1